2015
DOI: 10.1371/journal.pone.0138602
|View full text |Cite
|
Sign up to set email alerts
|

The Wound Healing and Antibacterial Activity of Five Ethnomedical Calophyllum inophyllum Oils: An Alternative Therapeutic Strategy to Treat Infected Wounds

Abstract: Background Calophyllum inophyllum L. (Calophyllaceae) is an evergreen tree ethno-medically used along the seashores and islands of the Indian and Pacific Oceans, especially in Polynesia. Oil extracted from the seeds is traditionally used topically to treat a wide range of skin injuries from burn, scar and infected wounds to skin diseases such as dermatosis, urticaria and eczema. However, very few scientific studies reported and quantified the therapeutic properties of Calophyllum inophyllum oil (CIO). In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 37 publications
2
52
0
1
Order By: Relevance
“…Recently, it has been reported that Tamanu oil enhanced the wound closure of a breach made on a monolayer of HaCaT cells [15]. In this study, Tamanu oil from Polynesia diluted with olive oil exhibited the highest wound closure compared to other Tamanu oils from Indonesia, the Fiji Islands, and New Caledonia.…”
mentioning
confidence: 50%
See 1 more Smart Citation
“…Recently, it has been reported that Tamanu oil enhanced the wound closure of a breach made on a monolayer of HaCaT cells [15]. In this study, Tamanu oil from Polynesia diluted with olive oil exhibited the highest wound closure compared to other Tamanu oils from Indonesia, the Fiji Islands, and New Caledonia.…”
mentioning
confidence: 50%
“…In addition to independent long-term traditional uses, the effectiveness of "Tamanu oil" was also proven by in vivo studies performed on hospitalized patients showing that its topical application on resistant wounds led to significant diminution of scars and impressive wound healing including postsurgical treatments [10,11]. Literature data revealed interesting biological activity related to skin affections and Tamanu oil content beneficial effects such as antibacterial [12], antifungal [13], antiinflammatory [14], and wound healing [15]. Such biological properties may explain the use of Tamanu oil as an active cosmetic ingredient Abstract !…”
mentioning
confidence: 99%
“…Calophyllum (Calophyllum inophyllum L., Calophyllaceae) is an evergreen tree found on the seashores and islands of the Indian and Pacific Oceans. Oil obtained from the seeds, also called Tamanu oil, is traditionally used dermally in French Polynesia to treat skin injuries (burns, scars, and infected wounds) and diseases (dermatosis, urticaria, and eczema; Ansel et al, ; Léguillier et al, ). In Vietnam, the oil has been used as a traditional medicine to treat burns, skin‐related and rheumatic diseases, and insomnia (Nguyen et al, ).…”
Section: Monounsaturated Fatty Acid‐based Butters/oilsmentioning
confidence: 99%
“…Calophyllum seeds have also been shown to contain many other chemical compounds, including inophyllum A-E, calophyllic acid, coumarins, phenols, polyphenols, triterpenoids, and flavonoids [16,[19][20][21][22][23]. As a result, the oil produced from Calophyllum seeds is widely used as a traditional medicine and in cosmetics, and as a lamp oil.…”
Section: Introductionmentioning
confidence: 99%